Target Tracking Algorithm Using Angular Point Matching Combined with Compressive Tracking. (10th November 2015) - Luo, Jing; Dong, Tingting; Zi, Chunyuan; Xiu, Chunbo; Tian, Huixin; Xi, Jiangtao
Abstract : To solve the problems of tracking errors such as target missing that emerged in compressive tracking (CT) algorithm due to factors such as pose variation, illumination change, and occlusion, a novel tracking algorithm combined angular point matching with compressive tracking (APMCCT) was proposed. A sparse measurement matrix was adopted to extract the Haar-like features. The offset of the predicted target position was integrated into the angular point matching, and the new target position was calculated. Furthermore, the updating mechanism of the template was optimized. Experiments on different video sequences have shown that the proposed APMCCT performs better than CT algorithm in terms of accuracy and robustness and adaptability to pose variation, illumination change, and occlusion.